Spatiotemporal changes and influencing factors of the intensity of the agricultural water footprint in Xinjiang, China - Wang, Yanyun; Long, Aihua; Deng, Xiaoya; Abulizi, Abuduaini; Wang, Jie; Zhang, Pei; Hai, Yang; Ren, Cai; Zhang, Ji; Liu, Yundong; Zhao, Weiming (International Journal of Agricultural and Biological Engineering, 2023)
Xinjiang Uygur Autonomous Region, the largest agricultural high-efficiency water-saving arid area in China, was adopted to explore the coupling relationship between agricultural water consumption and economic benefits, which is of great significance to guiding the efficient utilization and sustainable development of agricultural water resources. This study utilizes an indicator, termed the Agricultural Water Footprint Intensity (short as AWFI, which means the amount of water resource consumed per unit of agricultural GDP), to study the economic benefits of agricultural water in Xinjiang from 1991-2018. In addition, the Theil index, a measure of the imbalance between individuals or regions, was used to study the evolution in the spatial differences in water efficiency, and the Logarithmic Mean Divisia Index (LMDI) method was applied to quantify the factors driving the AWFI. The results showed that AWFI in Xinjiang has experienced three stages: obvious decline, stable and slow decline, which decreased from 16 114 m3/104 CNY to 2100 m3/104 CNY, decreasing by 86.97%. The Theil index indicated that the spatial evolution of 14 prefectures (cities) resembled an inverted N-shaped Kuznets curve over time. Among the influencing factors, the contributions of water-saving technology and planting structure to the change in the AWFI in Xinjiang, China from 1991 to 2018 were 154.03% and −37.98%, respectively. The total contribution to AWFI of the total population, urbanization rate, and production scale was −16.06%. This study concluded that further improvements in the economic benefits of agricultural water consumption can be obtained by continuing to promote more efficient or “water-conservation” irrigation technologies (engineering aspects), adjusting the planting structure (policy guidance aspects), and intensive management of cultivated land (management aspects).Keywords: agricultural water footprint intensity, Theil index, logarithmic mean Divisia index, XinjiangDOI: 10.25165/j.ijabe.20231603.7058Citation: Wang Y Y, Long A H, Deng X Y, Abulizi A, Wang J, Zhang P, et al. Spatiotemporal changes and influencing factors of the intensity of the agricultural water footprint in Xinjiang, China. Int J Agric & Biol Eng, 2023; 16(3): 262–272.